Rural Associations and Cooperatives: Internal and External Factors That Influence Their Stability and Efficiency. A Reflection on the Case of Viotá, Cundinamarca - Narváez Rodríguez, Cristhian Camilo (Cooperativismo & Desarrollo, 2014)
The development of efficient rural cooperatives with staying power over the long term is a fundamental element for agricultural development in Colombia. This research therefore looks at internal and external factors associated with such organizations, which affect their permanence and efficiency in the national rural context. The internal factors refer to the management capacity of these organizations to better handle organization, jointly with their associates. The external factors involve levels of institutional stability and interpersonal trust in the communities where the organizations operate. The document also reflects on the situation of three rural associations in the municipality of Viotá (Cundinamarca) in accordance with some of the referred-to factors.
Keywords: rural associations; efficiency; institutional stability; firms.